Juridical Review of Copyright Infringement Based on Law Number 28 of 2014 concerning Copyright (Case Study of Decision Number 338/Pdt.G./2020/PN. Jkt. Pst Year 2022) - Syailendra Putra, Moody Rizqy; Yunita, Theresia; Mayvians, Tidelstein (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Indonesia is a constitutional state where every action of its people has legal consequences. If you violate certain things, that person may be subject to sanctions under applicable law. One violation that often occurs in society is a violation of someone's copyright. For example using the Mall Grand Indonesia logo on the image/sketch of Almi's welcome monument. In this article, the author analyzes the case of the Selamat Datang Monument which was abandoned by the Alm family. Henk Ngantung for Grand Indonesia who allegedly erected a monument which ended with a damages penalty. Copyright infringement is regulated in the Copyright Law No. 28 of 2014. In this study, the authors conducted normative legal research using a legal approach, case approach and analytical approach.